(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze students’ experiences in using Augmented Reality (AR) applications as a learning medium for Automatic Transmission. This quantitative study involved students from SMK Negeri 1 Kuningan and aimed to address the challenges of visualizing complex material. Data were collected through questionnaires and analyzed using simple linear regression within the Technology Acceptance Model (TAM) framework. The results indicate that AR Content Quality has a positive and significant influence on Student Experience (R² = 0.558; p < 0.001; coefficient = 0.73). The regression model was found to be significant overall (F = 85.839; p < 0.001). This positive experience was found to enhance students’ interest, understanding, and engagement in the learning process. Thus, AR applications with high-quality content significantly facilitate better learning and support the acceptance of technology as a learning tool. These findings have important implications for the development of technology-based curriculum and teaching strategies in vocational schools.